Developing a Business Maturity Framework (BMF) in the Oil and Gas Industry - Panduru, Dan Andrei; Scarlat, Cezar; Ioanid, Alexandra (European Journal of Sustainable Development, 2024)
This study explores the utility of business maturity models in navigating dynamic business landscapes. It assesses existing models, develops an industry-specific Business Maturity Framework (BMF), and emphasizes foundational considerations for effective implementation aligned with organizational goals. The study concludes by highlighting the perpetual nature of business maturity and the BMF’s efficacy in enhancing operational excellence, competitiveness, and sustainable growth in the oil and gas sector. The paper contributes to specialized literature by introducing a novel dimension that evaluates market and customer readiness for future digitalization levels, thereby providing a comprehensive approach to business maturity. Keywords: business transformation, digital process maturity, business maturity framework (BMF), incremental changes, maturity assessment, disruptive changes, oil and gas industry